2011
DOI: 10.4236/eng.2011.311136
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Pressure for the Formation of YBa2Cu3O7–d Bulk Ceramics with Domestic Microwave Oven

Abstract: We fabricated YBa 2 Cu 3 O 7-d bulk ceramics with a domestic microwave oven and investigated the effect of pressure at the press procedure. If the pressure was not high enough, the ratio of BaCuO 2 phase became large, estimated from x-ray diffraction (XRD) measurements. We found that the pressure should be 700 kgf/cm 2 at least in order to suppress the BaCuO 2 phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Currently, the work is focused on improving the efficiency of the process of obtaining this superconductor and reducing production costs. Many modifications of this process are also proposed, e.g., the use of weak microwaves during YBCO synthesis, the replacement of BaCO 3 with BaO [17].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, the work is focused on improving the efficiency of the process of obtaining this superconductor and reducing production costs. Many modifications of this process are also proposed, e.g., the use of weak microwaves during YBCO synthesis, the replacement of BaCO 3 with BaO [17].…”
mentioning
confidence: 99%
“…There has been virtually no works on the dependence of properties on the technological parameters of obtaining solid YBCO material. One of the few works is that of Ohmukai [17], which dealt with microwave annealing and studied the influence of pressure during YBCO molding in the range of 80-2000 kgf cm −2 (about 7. . He concluded that in order to minimise the undesirable phase of BaCuO 2 in YBCO, the pressure should be 700 kgf cm −2 (about 68.6 MPa) [17].…”
mentioning
confidence: 99%
See 1 more Smart Citation